Effect of Platelet-Derived Growth Factor C on Mitochondrial Oxidative Stress Induced by High d-Glucose in Human Aortic Endothelial Cells - Adriana Grismaldo Rodríguez; Jairo A. Zamudio Rodríguez; Cindy V. Mendieta; Sandra Quijano Gómez; Sandra Sanabria Barrera; Ludis Morales Álvarez (MDPI AG, 2022)
Endothelial dysfunction is an early marker for cardiovascular diseases. Hyperglycemia induces endothelial dysfunction, increasing the production of reactive oxygen species. Platelet-derived growth factor C stimulates angiogenesis and revascularization in ischemic tissues of diabetic mice and promotes the migration of progenitors and mature ECs to injury sites; however, the molecular mechanisms of its actions are not described yet. Here, we evaluated the effect of PDGF-C on oxidative stress induced by HG. Human aortic endothelial cells were grown in glucose concentrations ranging from 5 mmol/L to 35 mmol/L for 1 to 24 h. Treatment with 50 ng/mL PDGF-C was done for 1 to 3 h. Cytosolic and mitochondrial ROS were measured by fluorometry, and the expression of antioxidant enzymes was evaluated by Western blot. Nrf2 and Keap1 expression was assessed by real-time PCR. High glucose induced mitochondrial ROS production. PDGF-C diminished the oxidative stress induced by high glucose, increasing SOD2 expression and SOD activity, and modulating the Keap1 expression gene. These results give new evidence about the mitochondrial antioxidant effect that PDGF-C could exert on endothelial cells exposed to high glucose and its considerable role as a therapeutic target in diabetes.